Conversational Implicature in Poetic Discourse – Selected Examples from Poems in the Middle School Arabic Language Textbook - .laouidji, ammar; choudar, ouahiba (El Omda in Linguistics and Discourse Analysis, 2022)
Abstract : ‘Grace’ sees when he dealt with the phenomenon of’conversational implicatur.that the sentence often carries two connotations,the first representsits direct superficial meaning,while the second is the indirect deep connotation indicated by the context in whic it was mentioned. A sufficient semantic interpretation of many sentences becom difficult in case it limited only on apparent data.which requires another semantic interpretation.According ,We aim,through this research paper,to reveal the poetic discourse linked by‘Speaker,listener,and intentions of this speaker .